Perancangan Prototype Sistem Informasi Rawat Jalan pada RSU Aisyah Padang Tahun 2022 - Syamsul Kamal; Yuli Mardi; Rindy Sakila (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Prototype design is a software development method that uses an approach to make designs quickly and gradually so that potential users can immediately evaluate the advantages and disadvantages of the designed prototype. With this prototyping method, developers and users can interact and communicate with each other during the process of making prorotypes. In the design of an outpatient information system prototype it is very necessary and needed is supporting data so that the design can be further developed and aligned with existing systems in hospitals. “Aisyiyah Padang. The design of the outpatient medical record information system in the hospital already exists and needs to be analyzed again whether it is relevant for the future or not. In designing the outpatient information prototype used DFD (Data Flow Diagram), ERD (Entity Relation Diagram), direct interview method with hospital medical record staff and IT to retrieve the information needed in the design and completion. The purpose of this research is to see and analyze how far the information system design is currently running, especially the outpatient department and see the weaknesses in designing this system and whether the current system design is useful for hospitals or is it still relevant today and what needs to be developed more specifically, analyzing the specifications of the requirements and system design, designing the system interface, and evaluating the results of the system analysis and design. The results obtained after conducting research at the Aisyiyah General Hospital are the need to develop a prototype outpatient information system that is currently running because there are still deficiencies and weaknesses in the design of the old system, which is no longer relevant to the current condition of the information system.